Stabilitas Vitamin D3 pada Dadih (Susu Kerbau Fermentasi) - Sari Bema Ramdika; Diana Nur Afifah; Anang Mohamad Legowo; Muflihatul Muniroh; Yora Nindita; Endang Mahati (Poltekkes Kemenkes Padang, 2023)
Vitamin D deficiency and inadequacy is a worldwide problem that can cause serious health problems. Vitamin D reduce the risk of osteoporosis, cancer, diabetes mellitus, and cardiovascular disease. Vitamin D is obtained from four sources such as sun exposure, food, supplements and fortification food. The research was conducted in October 2019. The purpose of this study was to see the stability of vitamin D3 in dadih during storage. The High Performance Liquid Chromatogaphy (HPLC) method was used to calculate vitamin D3 levels in fortified dadih. Quantification of vitamin D3 was done on day 0, day 3, day 9, day 16, day 23 and day 30. Statistical analysis showed that there was no significant difference in the level of vitamin D3 in dadih for 30 days of storage although there was a decrease in the level of vitamin D3 in dadih on the fourth week but it was not significantly (p> 0.05). In conclusion, Vitamin D3 in the dadih was stable for 30 days of storage although there was a decrease in vitamin D3 levels on the 16th and 30th days of storage due to the undetectable vitamin D3 in some samples. The addition of vitamin D3 to dadih is suggested using encapsulation techniques to increase solubility, longer shelf life, prevention of chemical degradation, better dispersibility, higher bioavailability and effectiveness.